Obituary: Kalliope Kritikakou-Nikolaropoulou - Zournatzi, Antigoni (Tekmeria, 2025)
In Memoriam: Kalliope Kritikakou-Nikolaropoulou (1959-2024) We remember Dr. Kalliope Kritikakou-Nikolaropoulou, a long-time member of the Editorial Committee of Τεκμήρια, who passed away on January 6, 2024. Dr. Kritikakou-Nikolaropoulou was a researcher at the National Hellenic Research Foundation, specializing in the epigraphy and history of Roman-Byzantine Palestine and Arabia. Her scholarly work on Greek inscriptions from Ghor es-Safi and the chronological systems of the region received the Prize of the Academy of Athens in Letters and Fine Arts (2006). Throughout her forty-year career, she was highly regarded for her collaborative spirit and devotion to her field. She will be remembered by colleagues for her genteel disposition, genuine kindness, and care for others.